Comercio electrónico y calidad de servicio en el Hospedaje Central Bed & Breakfast, Iquitos 2025 - Ramirez Perez, Victoria Gimena (2025)
Objective: To determine the influence of e-commerce on the quality of service at Hospedaje Central Bed & Breakfast, Iquitos 2025 Methodology: correlational, descriptive, non-experimental design research. Sample: 218 customers Guests of Hospedaje Central Bed & Breakfast Results: the variable e-commerce in its dimensions digital platforms, booking methods and online payment are related to the dimensions of service quality in its dimensions perception of the service, experience in the service and standardization of the Service with (p< 0.005). It is only not significant E commerce with its dimension Online booking and payment methods is not associated with service quality in its dimensions perception of service and standardization of service (e>0.005). In conclusión, e-commerce influences the quality of service at Hospedaje Central Bed & Breakfast, Iquitos (p=0.000)